University-Community Partnership of Work-Integrated Learning for Preservice Teachers as Support to Primary Rural Schools - Dlamini, Moeketsi Elias (Studies in Learning and Teaching, 2025)
This qualitative paper reports on the work-integrated learning of preservice teachers in two primary rural schools implementing multigrade teaching as support to schoolteachers. The problem in this study is that it is not common for preservice teachers to do their work integrated learning in multigrade schools. The aim of this study is to use work-integrated learning of preservice teachers as support to teachers teaching in rural primary schools. The study is couched in critical emancipatory research as the theoretical framework to empower and engage participants in the research study. Participants in this study were ten purposefully selected preservice teachers from one university and four experienced teachers, two from one of two primary schools. Participatory action research with focus group discussions was used to generate data. Data were analyzed using thematic analysis by identification and reporting of patterns. The findings revealed that work-integrated learning of preservice teachers provides support to teachers in rural schools. The study suggests a continuous working relationship between rural schools and the teacher education institutions. The recommendation in this study is for teacher education institutions to support teachers in rural schools by sending preservice teachers to rural schools during work-integrated learning.